2017
DOI: 10.1038/nm.4447
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone inhibits lung fibrosis in mice by improving epithelial mitochondrial function

Abstract: Thyroid hormone (TH) is critical for the maintenance of cellular homeostasis during stress responses, but its role in lung fibrosis is unknown. Here, we found that the activity and expression of iodothyronine deiodinase 2 (DIO2), an enzyme that activates TH, was higher in lungs of patients with idiopathic pulmonary fibrosis compared to control individuals and correlated with disease severity. We also found that Dio2 knockout mice exhibited enhanced bleomycin-induced lung fibrosis. Aerosolized TH delivery incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
263
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(282 citation statements)
references
References 65 publications
(82 reference statements)
17
263
1
1
Order By: Relevance
“…In this study, the expression of PGC‐1α was increased in IPF‐LFs and senescence‐induced Ctrl‐LFs. However, Yu et al recently reported that levels of PGC‐1α protein were decreased in lung homogenates of IPF patients (even though levels of its mRNA were increased). The PGC‐1α detected in lung lysates by immunoblotting was comparable in size to the PGC‐1α1 isoform, which has a predicted MW of 92 kDa, with lower MW forms not described or shown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression of PGC‐1α was increased in IPF‐LFs and senescence‐induced Ctrl‐LFs. However, Yu et al recently reported that levels of PGC‐1α protein were decreased in lung homogenates of IPF patients (even though levels of its mRNA were increased). The PGC‐1α detected in lung lysates by immunoblotting was comparable in size to the PGC‐1α1 isoform, which has a predicted MW of 92 kDa, with lower MW forms not described or shown.…”
Section: Discussionmentioning
confidence: 99%
“…3B). PGC1α is a transcriptional co-activator responsible for regulating genes required for mitochondrial biogenesis and cell energy expenditure, and is protective in experimental lung fibrosis (Yu et al, 2018). ARHGAP12 and ARHGAP29 are small Rho-binding subfamily members whose function has recently been highlighted as being critical for YAP/TAZ inactivation (Meng et al, 2018), major regulators of fibroblast activation in fibrosis (Liu et al, 2015).…”
Section: Hdac Inhibition Blocks Gene Expression Changes Associated Wimentioning
confidence: 99%
“…To investigate whether TGFβ-mediated repression of anti-fibrotic genes precedes TGFβ-mediated upregulation of pro-fibrotic genes, we examined the effect of TGFβ on select genes identified in Figs 3B and 4A over time. For anti-fibrotic genes, we selected PGC1α, ARHGAP12 and DACH1 due to their reported anti-fibrotic effect in fibrosis and fibroblasts (Lynch et al, 2018;Peng et al, 2017;Sandner and Stasch, 2017;Yu et al, 2018) in addition to their robust upregulation in the presence of pracinostat (Fig. 3B).…”
Section: Hdac Inhibition Blocks Gene Expression Changes Associated Wimentioning
confidence: 99%
“…Microarray Analysis: Geo2R (53) was used to analyse GSE47460 generated by the lung genome research consortium (54).…”
Section: Uk Biobankmentioning
confidence: 99%